Training and Development of an Anti-Bullying Task Force Based on a Peer Support System to Improve Student’s Psychosocial Safety at SMP Plus Darussalam Blokagung Banyuwangi - Abdul Karim; Indifatul Anikoh; Halimatus Sa'diah; Nurin Baroroh (Simfoni Ilmu Cindekia, 2025)
This Community Service Program (PkM) was implemented to address the urgent needs of SMP Plus Darussalam Blokagung, Banyuwangi, which lacks a formal mechanism for preventing and handling bullying. This activity aims to establish a peer-supported Anti-Bullying Task Force through a Participatory Action Research (PAR) approach that emphasizes empowering and strengthening the capacity of students and teachers in detecting, reporting, and responding to bullying cases. Interventions provided included anti-bullying literacy training, conflict management workshops, role-playing simulations, assistance in developing reporting SOPs, task force formation, and a safe school campaign. Participants in the activity consisted of 50 students and 10 supervising teachers. Program evaluation was conducted through observation, short interviews, FGDs, pre-post questionnaires, and activity documentation. The implementation results showed an increase in student knowledge and awareness regarding forms of bullying as well as empathetic communication skills. Students demonstrated greater courage in reporting, and the task force began carrying out initial mediation functions in several minor cases. In addition to increasing individual capacity, the school acquired a new institutional structure in the form of an Anti-Bullying Task Force and a participatory reporting SOP. These findings indicate that the PAR approach is effective in strengthening the school community's ability to create a safe and supportive learning environment. The program also demonstrates potential for sustainability through the integration of task force activities into the school's agenda, as well as opportunities for replication in other schools with similar needs.